Plant diversity along a disturbance gradient in a semi-arid ecosystem in Central Mexico - Osvaldo Eric Ramírez-Bravo (Acta Botanica Mexicana, 2016)
Background and Aims: Habitat fragmentation and other human disturbances can cause loss of soil fertility, erosion, biodiversity, among others; however, available information in arid regions is limited. Our aim was to determine the effects of a disturbance gradient on species composition in two vegetation types in a semi-arid area of central Mexico. Methods: We selected six patches, three of shrubland and three of tropical dry forest, in the area of Cerro Colorado. We quantified the species and generic diversity of ten quadrats per patch (60 in total), placed randomly, during the months May-June 2011. We developed a disturbance index based on disturbances such as grazing and wood use among others. High, medium and low disturbance areas were identified in both tropical dry forest and shrubland. Key results: Results indicate that tropical dry forest is more diverse than shrubland. The shrubs Cnidoscolus tehuacanensis and Mimosa luisana were indicators of disturbance as they are found in higher relative abundance in highly disturbed quadrats. In tropical dry forest, three genera (Thevetia, Acacia and Bursera) showed higher relative abundance in conserved patches while in shrubland only one (Parkinsonia) shows this pattern, hence they could serve as indicator species. Conclusions: Our results provide evidence that disturbance in semi-arid areas of central Mexico plays an important role in species composition, facilitating the establishment of certain native species that can be considered colonizer species. These native species could be used as indicators of disturbance in assessing habitat suitability for different species.